Fenologia e comportamento de parasitoidismo de Spalangia endius Walker, 1839 (Hymenoptera, Pteromalidae) em condições de laboratório - Araújo, Dani Furtado de (2011)
Synantropic flies frequently reach the status of plague in urban and rural areas, assuming an important role regarding its vectorial ability and nuisance to men and animals. Therefore, it is necessary to know their natural enemies in order to achieve a satisfactory control of these dipterans. The success of the biological control as an alternative to the Integrated Pest Management depends on the evaluation of enemies as potential control agents through the development of breeding techniques and laboratory evaluations. Considering that, this study had as objective to understand the phenology of Spalangia endius as well as the parasitoidism of this species using M. domestica, Muscina stabulans and Chrysomya megacephala as hosts, being the last two potential alternative hosts. Colonies of S. endius, M. domestica, M. stabulans e C. megacephala were kept in climatized chamber, at 26ºC ± 2, relative air humidity ≥70% and 12 hours photophase. In order to know the phenology of S. endius, 360 pupae of Musca domestica with ages ranging from 24 to 48 hours were exposed to 15 couples of S. endius for a period of 48 hours at 26ºC ± 2. These pupae were kept in B.O.D chambers at the same conditions of the climatized chamber, where 15 specimens were dissecated to observe the stage and the development time of the hymenopteran. The phenology allows concluding that S. endius presents a development cycle (egg-adult) of 19 to 31 days, with an incubation period of 24 hours, the development of the larvae of S. endius occurred in the 12 subsequent days, in which a series of morphological alterations were observed. The pre-pupae stage occurred in the tenth day where the movement ceased and the meconium elimination begun. The pupal stage occurred in at least 8 and at maximum 12 days, ending the cycle with the emergence of males and around 24 hours later, the emergence of females. The parasitoidism on thet host species was higher in M. domestica with 63%, followed by M. stabulans and C. megacephala with 27,5% and 16,5% respectively. The morphometrical measures confirmed the preference for M. domestica due to the higher size of the parasitoids that developed in this host. There was no significant difference regarding to the size of the parasitoids that developed in pupae of M. stabulans and C. megacephala as well as there was no influence of the sex in the size of the parasitoid. The data here obtained on the parasitoidism of S. endius in the different hosts show that under the studied conditions the best host is M. domestica. Based on the phenology of S. endius, further detailed studies can be carried out in order to optimize the breeding of this parasitoid in laboratory conditions, allowing the biological control of M. domestica as well as M. stabulans e C. megacephala.